Open regionalism and economic integration. - FUENTES, Juan Alberto (1994)
Notes that economic integration in Latin America is conditioned by new development strategies directed at adjusting to a changed and increasingly demanding world economy. Identifies some of the obstacles likely to be faced by economic integration in the future.